Faktor Yang Memengaruhi Pernikahan Usia Muda Pada Pasangan Suami Istri di Desa Tanjung Mompang Kec. Panyabungan Utara Kab. Mandailing Natal - Lubis, Desy Hermarani; Suroyo, Razia Begum; Sibero, Jitasari Tarigan (Fakultas Kesehatan Masyarakat Universitas Muslim Indonesia, 2020)
Young marriage is marriages performed by men under the age of 19 years and women under the age of 16 years. According to WHO in 2014 showed amount 16 million women gave birth aged 15-19 years or 11% of all births in the World this study aims to analyze the factors that influence young marriage in a married couple at Tanjung Mompang Village, North Panyabungan District of Mandailing Natal Regency in 2019. This research uses a mix method research. The populations were husband and wife couples with fertile age status who engaged in young marriage amount 79 couples. The quantitative approach sample was 79 married couples. The qualitative approach was 3 married couples, 1 village head, 1 village midwife, 1 traditional leader. Quantitative analysis was done by univariate, bivariate, multivariate analysis. Qualitative analysis performed by data reduction, data presentation, and drawing conclusions. The results showed the majority of knowledge variables lack p-value .038, majority education low value p-value .013, parenting majority lack p-value .011, majority culture supports p-value .025. The conclusion shows that there is the influence of knowledge, education, parenting, and culture. The most dominant variable affecting young marriage is culture. It is expected that traditional leaders can provide a way of life for adolescents not to engage in young marriage and suggestion for adolescents to study to college to be useful adolescents, thus the teenager knows the negative effects of young marriage that are vulnerable to reproductive health problems.